Exploring students’ imaginative process: Analysis, evaluation, and creation in mathematical problem-solving - Sri Rahayuningsih; Muhammad Nurhusain; Sirajuddin Sirajuddin (Beta: Jurnal Tadris Matematika, 2023)
[English]: The role of imagination as a means of learning mathematics, unlike in other fields such as art and literature, is not well defined. The present study aims to examine the process of students’ imagination in solving mathematics problems. It involved three grade 8 students which were purposively selected based on their scores in a given test. Students’ answers to the test and the results of interviews were examined qualitatively referring to the three stages of creative problem-solving that involve imagination: analysis, evaluation and creation. The results show that, in the analysis phase, imagination was found in the students’ ability to define problems in general (common visual). As the first step in solving a problem, they analysed mathematical knowledge needed to solve the problem. In the evaluation phase, imagination was formed as students completed the final answer by creating visual representations from previous experiences as artifacts taken together and gathering necessary knowledge. In the last phase, creation, imagination was identified when students engaged in a cyclical thought process to find new ideas in solving the problem. This process repeated until the students found no other ideas or ways to solve the problem. [Bahasa]: Peran imajinasi sebagai sarana belajar matematika belum didefinisikan dengan baik, tidak seperti pada bidang lain seperti seni dan sastra. Penelitian ini bertujuan menelusuri proses imajinasi siswa selama melakukan pemecahan masalah matematika. Penelitian ini melibatkan tiga siswa kelas 8 yang dipilih melalui purposive sampling, berdasarkan nilai tertinggi hasil tes pemecahan masalah matematika. Jawaban siswa dan hasil wawancara dianalisis secara kualitatif dengan merujuk pada tiga tahapan proses kreatif yang melibatkan imajinasi: analisis, evaluasi dan kreasi. Hasil penelitian menunjukkan, pada tahap analisis, imajinasi yang terbentuk ditandai dengan kemampuan siswa menetapkan masalah secara umum (common visual). Sebagai langkah awal untuk menyelesaikan masalah, siswa melakukan koreksi dengan cara memikirkan kembali pengetahuan matematika yang dibutuhkan. Proses imajinasi pada tahap evaluasi ditunjukkan oleh kemampuan siswa dalam menyimpulkan jawaban akhir dengan cara membangun visual dari pengalaman sebelumnya sebagai artefak yang diambil bersama serta mengumpulkan pengetahuan yang diperlukan. Pada tahap kreasi, kemampuan siswa melakukan proses berpikir secara siklis dalam memikirkan ide baru untuk menyelesaikan masalah yang dihadapi menunjukkan proses imajinasi pada tahap ini. Proses ini berlangsung secara berulang, sampai siswa tidak memiliki ide lagi untuk menyelesaikan masalah.